2020
DOI: 10.3390/gels6020013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and 3D Printing of Conducting Alginate–Polypyrrole Ionomers

Abstract: Hydrogels composed of calcium cross-linked alginate are under investigation as bioinks for tissue engineering scaffolds due to their variable viscoelasticity, biocompatibility, and erodibility. Here, pyrrole was oxidatively polymerized in the presence of sodium alginate solutions to form ionomeric composites of various compositions. The IR spectroscopy shows that mild base is required to prevent the oxidant from attacking the alginate during the polymerization reaction. The resulting composites were isolated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The films made from compositions with concentrations higher than 2 ml of PPy were fragile, so they were broken to pieces during the drying process or within evaluation of their surfaces by four-point probe. These results were consistent with previous studies in which showed more PPy concentration more fragility of film 10 , 21 , 22 . As a result, the composite ratio 2:10 was chosen which provides a suitable mechanical property and electrical conductivity.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The films made from compositions with concentrations higher than 2 ml of PPy were fragile, so they were broken to pieces during the drying process or within evaluation of their surfaces by four-point probe. These results were consistent with previous studies in which showed more PPy concentration more fragility of film 10 , 21 , 22 . As a result, the composite ratio 2:10 was chosen which provides a suitable mechanical property and electrical conductivity.…”
Section: Resultssupporting
confidence: 94%
“…Alginate-based scaffolds were also used as an appropriate substrate for construction of conductive scaffolds based on pyrrole monomers using electrostatic interactions between carboxylate moieties of alginate and positively charged PPy 16 . Several studies have designed alginate-pyrrole based scaffolds or hydrogels with electrical properties for neural tissue engineering [21][22][23] .…”
mentioning
confidence: 99%
“…[ 101,104 ] While initial cell adhesion and survival was shown for PC‐12 cells, [ 101,104 ] the addition of gelatin in our study as a main hydrogel‐ink component, subsequently crosslinked by a transglutaminase, showed significantly increased cell‐material interaction and growth in comparison to this previous work (Figure 5). [ 101,104 ] In comparison to hyaluronic acid‐PPy hydrogels which have been prepared with electrical conductivities of up to 0.73 S m −1 and cytocompatibility with respect for NIH‐3T3 fibroblast cells, [ 82 ] the hydrogels in our study showed increased cell‐material interaction, mostly associated to the presence of gelatin, as well as conductivities in a similar range of up to ≈1.6 S m −1 at high frequencies and >1 S m −1 in DC measurements. In addition, our hydrogels show 3D‐printability, which may be an advantage over previously introduced PPy‐X systems.…”
Section: Discussionmentioning
confidence: 48%
“…ALG‐PPy hydrogel has recently been engineered to allow 3D‐printability for direct extrusion after PPy in situ formation. [ 101 ] However, as ALG lacks controlled degradation as well as binding sites for cell‐interaction, [ 98 ] we introduce ADA‐GEL‐PPy, with its main advantages of higher degradation and cell attachment potential provided by ADA‐GEL [ 98 ] in comparison to pristine ALG‐based PPy combinations. The degradation of the hydrogels could be tuned by reducing transglutaminase content in the crosslinking step, [ 55 ] which dictates the degradation behavior, as ADA‐GEL‐PPy showed similar swelling and degradation as the ADA‐GEL reference.…”
Section: Discussionmentioning
confidence: 99%
“…The atmospheric pressure plasma polymerization has different advantages, such as it works at room temperature waterless process and little-cost habitual continuance. This method is appropriate for using many types of substrates without being damaged by heat on these slides [6][7][8]. The characteristics of prepared polypyrrole thin films by plasma jet system could be superior with high deposition rate thanks to most favorable discharge gas flow rate [9][10][11].…”
Section: Introductionmentioning
confidence: 99%